NutriQuébec: a unique web-based prospective cohort study to monitor the population's eating and other lifestyle behaviours in the province of Québec. Issue 10 (28th October 2020) - Lapointe, Annie; Laramée, Catherine; Belanger-Gravel, Ariane; Buckeridge, David L; Desroches, Sophie; Garriguet, Didier; Gauvin, Lise; Lemieux, Simone; Plante, Céline; Lamarche, Benoit
Abstract : Introduction: The epidemic of non-communicable diseases including cardiovascular diseases and type 2 diabetes is attributable in large part to unhealthy eating and physical inactivity. In the fall of 2016, the Québec government launched its first-ever Government Health Prevention Policy (Politique gouvernementale de prévention en santé (PGPS)) to influence factors that lead to improved health status and quality of life as well as reduced social inequalities in health in the population of Québec. NutriQuébec is a web-based prospective open cohort study whose primary aim is to provide essential data for the evaluation of the PGPS on the Québec population's eating and other lifestyle behaviours over time. Methods and analysis: Over a first phase of 3 years, NutriQuébec will enrol 20 000 adults living in the province of Québec in Canada through a multimedia campaign designed to reach different segments of the population, including subgroups with lower socioeconomic status. Participants will be invited to complete on a web platform nine core questionnaires on a yearly basis. Questionnaires will assess several dimensions related to lifestyle, including eating and physical activity behaviours, as well as a large number of personal characteristics and global health status. Temporal trends in eating and lifestyle behaviours will be analysed in relation to the implementation of the PGPS to provide essential data for its evaluation at a population level. Data analyses will use sociodemographic weights to adjust responses of participants to achieve, so far as is possible, representativeness of the adult Québec population. Ethics and dissemination: Université Laval Research Ethics Board approved the NutriQuébec project. Data analysis, presentations in conferences and publication of manuscripts are scheduled to start in 2020. Trial registration number: NCT04140071 .